Gender budgeting and women empowerment in India - Singh, Awadesh K. (Awadesh Kumar), 1961-; Singh, S. P., 1966-; Sutaria, D. S.; Supath Gramodhyog Sansthan (New Delhi : Serials, 2010)
Papers presented at a national seminar held at Ahmedabad during 13-14 September 2008.
Includes index.
Includes bibliographical references.
Keywords: Budget process -- Social aspects -- India -- Congresses; Women in economic development -- India -- Congresses; Sex discrimination in national income accounting -- India -- Congresses